(3MGTjI Ydi TQM MceI GdYjfs - (3GdTjQGRj GdfLaj, eMeO WGgQ Hf eMeO MSjf GdTjQGRj, J (B1098(3g` (B1687(3es ((3GdeOQSI GdHGbhfjI HCQRf GdQhes)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B... (3bGd GdTGQM(B: (3GdMceI GSJceGd GdN GdGSJceGd eUOQ hGdeUGOQ bO JWdb hjQGO HgG eYGfjg GdfSHjI hbO JWdb hjQGO HgG GdMGUd HGdeUOQs
(3BNQgG (B:s
(3BNQgG(B: (3hdhcGf cPdc jdRe (B.. (3dG jecf ddYbd GdMce Ydi TgGOI ZjQ eJfGg eYOhe Ydi ZjQ eJfGg iNQ eYOhe HeLQO hLhOgeG aj GdYbd ajdRe Cf dG (B.. (3GdYbd Ydi JYGbdgeGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 366s
(3GdPQjYI, L (B6: 89s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs